Ameerika Ühendriikide maavägi ja Korea riiklik raudtee Korea sõja ajal 1950–1953. Sõjajõudude ja tsiviilorganisatsiooni vastastikuse koostöö juhtumiuuring [US Army and Korean National Railroad during the Korean War: 1950–1953] - Sibul, Eric Allan (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
This article examines how the US Army worked with the civilian Korean National Railroad (KNR) to provide logistics support to the United Nations (UN) forces during the Korean War in 1950–1953. During this conflict, railways were of paramount logistical importance to both the UN and the Communists. Korean railways were well suited for military transport as they were primarily developed by the Japanese between 1904 and 1945 to provide strategic transport between Korean ports and Manchuria.When the Korean War broke out in June 1950, South Korea’s KNR was a young and inexperienced organization, being formed just two years prior, and thus could not cope with wartime operation without outside assistance. (Longer version of the current abstract is included in the article, starting from p 142.)